DETERMINANTS OF DIABETES MELLITUS PREVENTION IN ADOLESCENTS: A SYSTEMATIC REVIEW - Nugroho Budi Setiawan; Edy Soesanto; Dera Alfiyanti (Pena Cendekia Insani, 2026)
Prediabetes and type 2 diabetes mellitus (DM) in adolescents are increasing globally, highlighting the need for early prevention. This study aimed to synthesize evidence on determinants of DM prevention among adolescents. A systematic review following PRISMA guidelines was conducted on studies published between 2020 and 2025. The results show that DM prevention is influenced by multilevel factors, including individual (knowledge and self-efficacy), behavioral (diet and physical activity), family support, school environments, and sociocultural context, with lifestyle and school-based interventions demonstrating the most consistent improvements in behavioral and metabolic outcomes. Inconclusion, effective DM prevention in adolescents requires integrated, multilevel strategies that address behavioral, psychosocial, and environmental determinants.